An Interorganellar Bidding War: Vps13 Localization by Competitive Organelle-Specific Adaptors. (November 2018) - Dziurdzik, Samantha K.; Bean, Björn D.M.; Conibear, Elizabeth
Membrane contact sites are regulated through the controlled recruitment of constituent proteins. Yeast vacuolar protein sorting 13 (Vps13) dynamically localizes to membrane contact sites at endosomes, vacuoles, mitochondria, and the endoplasmic reticulum under different cellular conditions and is recruited to the prospore membrane during meiosis. Prior to our recent work, the mechanism for localization at contact sites was largely unknown. We identified Ypt35 as a novel Vps13 adaptor for endosomes and the nucleus-vacuole junction. Furthermore, we discovered a conserved recruitment motif in Ypt35 and found related motifs in the prospore membrane and mitochondrial adaptors, Spo71 and Mcp1, respectively. All three adaptors compete for binding to a six-repeat region of Vps13, suggesting adaptor competition regulates Vps13 localization. Here, we summarize and discuss the implications of our work, highlighting key outstanding questions.